COVID-19 and oral diseases: Assessing manifestations of a new pathogen in oral infections. (13th July 2022) - Naqvi, Afsar R.; Schwartz, Joel; Brandini, Daniela Atili; Schaller, Samantha; Hussein, Heba; Valverde, Araceli; Naqvi, Raza Ali; Shukla, Deepak
Abstract: Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) is a recently identified virus responsible for life-threatening coronavirus disease 19 (COVID-19). The SARS-CoV-2 infected subjects can be asymptomatic or symptomatic; the later may present a wide spectrum of clinical manifestations. However, the impact of SARS-CoV-2 on oral diseases remain poorly studied. Detection of SARS-CoV-2 in saliva indicates existence of virus in the oral cavity. Recent studies demonstrating the expression of ACE-2, a SARS-CoV-2 entry receptor, in oral tissues further strengthens this observation. Cytokine storm in severe COVID-19 patients and copious secretion of pro-inflammatory cytokines (IL-6, IL-1β and TNF-α) in multiple symptomatic oral pathologies including periodontitis and periapical periodontitis suggests that inflammatory microenvironment is a hallmark of both COVID-19 and oral diseases. Hyperinflammation may provide conducive microenvironment for the growth of local oral pathogens or opportunistic microbes and exert detrimental impact on the oral tissue integrity. Multiple case reports have indicated uncharacterized oral lesions, symptomatic irreversible pulpitis, higher plaque index, necrotizing/desquamative gingivitis in COVID-19 patients suggesting that SARS-CoV-2 may worsen the manifestations of oral infections. However, the underlying factors and pathways remain elusive. Here we summarize current literature and suggest mechanisms for viral pathogenesis of oral dental pathology derived from oral microbiome and oral mucosa-dental tissue interactions. Longitudinal studies will reveal how the virus impairs disease progression and resolution post-therapy. Some relationships we suggest provide the basis for novel monitoring and treatment of oral viral disease in the era of SARS-CoV-2 pandemic, promoting evidence-based dentistry guidelines to diagnose virus-infected patients to improve oral health. Graphical Abstract: UF0001